2019
DOI: 10.1097/aog.0000000000003189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genetic Variants on Steady-State Etonogestrel Concentrations Among Contraceptive Implant Users

Abstract: This draft guidance represents the Food and Drug Administration's (FDA's) current thinking on this topic. It does not create or confer any rights for or on any person and does not operate to bind FDA or the public. An alternative approach may be used if such approach satisfies the requirements of the applicable statutes and regulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
1
27
2
Order By: Relevance
“…Like Zubiaur and colleagues, we utilized a candidate gene approach for our investigation, including genetic variants in CYP2C19, CYP2C9, and three other metabolizing enzyme genes (CYP3A4, CYP3A5, CYP3A7). However, unlike Zubiaur et al [1], we did not find that variants in CYP2C19 were associated with differences in serum etonogestrel concentrations among our 350 contraceptive implant users [2]. Alternatively, we found that a variant in CYP3A7 (the *1C variant) was significantly associated with 23% lower etonogestrel concentrations than the respective wild-type genotype [2].…”
Section: First Available Online On September 3 2019 Incontrasting
confidence: 94%
See 1 more Smart Citation
“…Like Zubiaur and colleagues, we utilized a candidate gene approach for our investigation, including genetic variants in CYP2C19, CYP2C9, and three other metabolizing enzyme genes (CYP3A4, CYP3A5, CYP3A7). However, unlike Zubiaur et al [1], we did not find that variants in CYP2C19 were associated with differences in serum etonogestrel concentrations among our 350 contraceptive implant users [2]. Alternatively, we found that a variant in CYP3A7 (the *1C variant) was significantly associated with 23% lower etonogestrel concentrations than the respective wild-type genotype [2].…”
Section: First Available Online On September 3 2019 Incontrasting
confidence: 94%
“…Advances in Therapy, Zubiaur et al [1] suggested that the CYP2C19 phenotype may help explain some of the variability in serum progesterone concentrations when taken orally or vaginally and stated that there are ''no other pharmacogenetic studies of progesterone'' with which to compare their results. In fact, our published pharmacogenomics study of etonogestrel metabolism is an important comparator [2]. Etonogestrel, a progestin found in some forms of contraception including the continuous-release subdermal implant, is metabolized in very similar processes to progesterone [3].…”
Section: First Available Online On September 3 2019 Inmentioning
confidence: 99%
“…A study of 350 healthy, reproductive-age women using etonogestrel implants for 12-36 months were genotyped for 14 genes encoding proteins involved in steroid hormone-related pathways. 60 Carriers of the CYP3A7*1C allele were more likely to have serum etonogestrel concentrations falling below the threshold of 90 pg/ mL required for consistent ovulatory suppression. This allele results in adult expression of the fetal CYP3A7 enzyme, which is in the same family as the CYP3A4 enzyme known to metabolize estrogens.…”
Section: Hormonal Contraceptionmentioning
confidence: 99%
“…1) may alter CYP specificity, (b) the endogenous nature of progesterone vs. the exogenous nature of etonogestrel and (c) the differences in the study population, i.e., postmenopausal women vs. contraceptive implant users. To be able to compare our results with those of Lazorwitz et al [1], it must be assumed that both compounds are metabolized in the exact same way. More difficult to assume are the limitations stated in ''(b)'' and ''(c)''.…”
mentioning
confidence: 95%
“…We are pleased to reply to Lazorwitz et al [1] letter response in regard to our manuscript published in Advances in Therapy on September 2019 [2]. First, we commend the efforts of Lazorwitz A. and colleagues in searching genetic factors that may influence etonogestrel plasma concentrations, especially for exploring Cytochrome P450 (CYP) enzymes as they have traditionally been considered of little relevance for the metabolism of progestogens.…”
mentioning
confidence: 99%